Mechanism of Shi-Yang-Xiao lotion in alleviating perianal eczema based on network pharmacology and experimental validation - Huang, Chuyue; Zhou, Bingwen; Duan, Meng; Zheng, Tuotuo; Tang, Yan; Liu, Qingrui; Dong, Yujing; Kong, Desong; Leng, Qiang; Wang, Lu; Fan, Zhimin (Frontiers in Molecular Biosciences, 2025)
BackgroundShi-Yang-Xiao lotion (SYXL), due to its anti-inflammatory and antipruritic properties, is widely used in treating Perianal Eczema (PE) with remarkable clinical efficacy. However, the chemical constituents of SYXL and its underlying mechanisms of action in treating PE remain to be elucidated.Aim of the studyTo elucidate the molecular mechanisms underlying the therapeutic efficacy of SYXL in treating PE by integrating network pharmacology techniques with experimental validation.Materials and methodsUltra Performance Liquid Chromatography–Quadrupole Time-Of-Flight–Mass Spectrometry/Mass Spectrometry (UPLC-QTOF-MS/MS) was utilized to identify the effective chemical constituents of SYXL. Potential targets and pathways were elucidated utilizing network pharmacology analysis. Subsequently, ELISA and Western blotting were utilized in a rat model of PE induced by DNCB, and in HaCaT cells co-stimulated with tumor necrosis factor-α (TNF-α) and interferon-γ for further validation.ResultsUPLC-QTOF-MS/MS identified a total of 93 compounds. Network pharmacology analysis revealed that the Janus kinase (JAK)/signal transducer and activator of transcription (STAT) signaling pathway was predicted to play major roles in the therapeutic effects of SYXL on PE. In vivo experiments demonstrated that SYXL ameliorated eczema-like skin lesions. Both in vivo and in vitro, SYXL inhibited the production of inflammatory cytokines, suppressed the phosphorylation of JAK2 and STAT3, thereby blocking the JAK-STAT signaling pathway.ConclusionOur findings indicated that SYXL repaired skin barrier, suppressed inflammation, and treated PE by decreasing the generation of interleukin-1β, interleukin-6, and TNF-α, as well as inhibiting the phosphorylation of JAK2 and STAT3.